THE ACCOUNTABILITY OF ZAKAT AL-FITR MANAGEMENT BY RELIGIOUS FIGURES AS ÂMIL AL-ZAKÂT - Lailatul Qadariyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This article aims to find out the accountability of zakat management done by the community leaders or Kiai who do not have documentation in funding and distribution. This study uses the case study approach, one of approaches in qualitative research, which uses interview and observation as the instruments of data collection. The result reveals that accountability, accounting, and functional perspectives have been fulfilled in the zakat management by Kiai. However, two of five characteristics of the accountability system perspective cannot be fulfilled by Kiai as âmil al-zakât, those are the written data presentation and the data publication. In other words, internally what Kiai does in the zakat management is very accountable. This is because of his science integrity and spirituality. In terms of external accountability loaded with document and neat presentation of data, Kiai somehow cannot fulfill it. This is because the period of management of zakat al-fitr is very short (only a few hours) and the target of zakat distribution is real and known.